PROBLEMS OF LIFE QUALITY ASSESSMENT AT POPULATION LEVEL - Ya. A. Leshchenko (Acta Biomedica Scientifica, 2013)
At present, many investigators pay their attention to studying the problem of life quality based on analysis of the objective and subjective indicators. Thereto, the numerous solutions, very unequal in both its objective grounding, choosing the concrete indices and in the methodical approaches used have been suggested. Moreover, the category of «life quality» is usually studied by the most authors at the individual level, rarely - at the group level. The specific category character «life quality» according to the big ethnological societies has been considered and the critical analysis of the available approaches to its study has been given in this work. The peculiarities of the population differentiation according to the levels of the material well-being in dependence on the salary sizes in the different branches of economy have been considered. The insufficient assessment of the society life quality in common extensive and averaged social-economic complex (the gross intrinsic product, the mean income level, the volume of the retail trades and so on) has been indicated. The complicity of reaching the wished life quality way he released informing the dangerous deformation of the adaptive strategies of the population. The sociological studies have shown that the increase in the deviant, extra-right strategies in the Russian society is the result of the reality adaptation of the available social-economic system, the method of the keeping and getting the wished life quality in contrast to all the eternal conditions and changes. The need of the population life quality assessment using the intensive, structural (qualitative) and social criteria (dependence on the world economic conjuncture, the quality of economics grows, the degree of the social-economic inequality, the registration or the oblivion of the requirements in the scientific-technical development, the problems of national safety) has been grounded. The society life quality assessment may not be considered as the adequate and complete if it is mainly based on the economic indices of vital activity (the level of the material well-being) and doesn't take into account the most important aspects such as the economic inequality, the social well-being, the state of human potential, the national safety and so on.